Effect of Intercropping, Elevation and Nitrogen Dose on Performance of Maize-mungbean Cropping Systems: Maize-Mungbean Intercropping for Sustainable Food Production - Arshad, Muhammad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
Monocropping of traditionally grown maize (Zea mays L.) on diverse elevations with inappropriate fertilizer dosage is leading to low land productivity and staple food insecurity in the mountainous areas. Therefore, a study was conducted to investigate the impact of replacing the traditionally grown maize variety with an improved variety and influence of elevation, intercropping and nitrogen (N) fertilizer levels on growth and yield of maize and mungbean (Vigna radiata L.) grown in different sole and mixed cropping systems. Field experiments were carried out using 3×3×3 factorial combination of three elevations (i.e., 1500 m, 1800 m & 2200 m above mean sea level), three cropping systems: i.e., sole maize (conventional and introduced cultivars) and intercropping (i.e., maize + mungbean), three N levels (i.e., 28, 56, 113 kg N ha-1) organized in a randomized complete block design layout. Plant height of maize and grain yield of both maize and mungbean were recorded after harvesting. Land Equivalent Ratio (LER) and nutritional parameters (i.e., carbohydrates, protein, fat and digestible energy) in harvested grains were computed. Higher (P ≤ 0.5) growth, yield and nutritional parameters were observed at elevation of 1500 m followed by 1800 m and 2200 m. Growth and yield components of introduced maize were higher compared to traditionally grown sole maize. Nutritional parameters (P ≤ 0.5) were greater for intercropping compared to sole cropping of maize. Despite a substantial reduction (P ≤ 0.5) in growth and yield components of mungbean in intercropped situation, its contribution to overall production led to increased LER (1.9) of the intercropping system over sole cropping of maize.